Insight into the plasma structure of the Quad Confinement Thruster using electron kinetic modelling. (August 2020) - Williams, Rhys David; Fabris, Andrea Lucca; Knoll, Aaron
Abstract: The behaviour of plasma within the discharge channel of the Quad Confinement Thruster is studied on the basis of electron kinetics. Here we propose that E × B drift of electrons drives the formation of unusual quadrant dependent light emitting structures observed experimentally in the discharge channel of the Quad Confinement Thruster. This assertion is made on the basis of a theory-based analysis and a computational model of the Quad Confinement Thruster. A particle orbit model of electron motion under the influence of applied electric and magnetic fields was used to assess electron transport. Structures strongly resembling that of the observed visible emission regions were found in the electron density distribution within the channel. While the motion of electrons cannot be decoupled from the motion of ions, as in this simple electron kinetic approximation, the results of this analysis strongly indicate the physical mechanism governing the formation of the non-uniform density distributions within the Quad Confinement Thruster channel. Highlights: A mechanism driving quadrant dependent light emission in the QCT is identified. E × B drift of electrons and ion ambipolar diffusion leads to a non-uniform plasma. Spatially non-uniformity plasma results in distinct light emitting structures. The mechanism is demonstrated using an electron kinetic model. Results suggest emissions are linked to E × B driven non-uniform electron density.